2014
DOI: 10.1210/en.2013-2046
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of MicroRNAs in Omental Adipose Tissue From Gestational Diabetes Mellitus Subjects Reveals miR-222 as a Regulator of ERα Expression in Estrogen-Induced Insulin Resistance

Abstract: Omental adipose tissue plays a central role in insulin resistance in gestational diabetes mellitus (GDM), and the molecular mechanisms leading to GDM remains vague. Evidence demonstrates that maternal hormones, such as estradiol, contribute to insulin resistance in GDM. In this study we determined the differential expression patterns of microRNAs (miRNAs) in omental adipose tissues from GDM patients and pregnant women with normal glucose tolerance using AFFX miRNA expression chips. MiR-222, 1 of 17 identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(105 citation statements)
references
References 35 publications
1
100
0
1
Order By: Relevance
“…However, this study was conducted in cultured IECs, and miR-222 has been considered to act as a tumor suppressor or oncogene in cancer development (12,(21)(22)(23); therefore, the exact function of miR-222 in the intestinal epithelium in vivo remains to be fully investigated. By using a tissue-specific transgenic expression approach, here we provided powerful genetic evidence that miR-222 plays an important role in the regulation of intestinal mucosal regeneration and protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study was conducted in cultured IECs, and miR-222 has been considered to act as a tumor suppressor or oncogene in cancer development (12,(21)(22)(23); therefore, the exact function of miR-222 in the intestinal epithelium in vivo remains to be fully investigated. By using a tissue-specific transgenic expression approach, here we provided powerful genetic evidence that miR-222 plays an important role in the regulation of intestinal mucosal regeneration and protection.…”
Section: Discussionmentioning
confidence: 99%
“…miR-222 modulates distinct cellular functions (17)(18)(19), and its role in cancer development can be either tumor suppressive or oncogenic, depending on cellular content and tumor type (20,21). miR-222 in human colorectal cancer cells acts in a positive feedback loop to increase expression levels of RelA and STAT3 (22), but miR-222 is a potential repressor of estrogen receptor (ER)-α expression in 3T3-L1 adipocytes (23). Our previous studies indicate that miR-222 and the RNA-binding protein (RBP) CUGBP1/CELF1 (CUG triplet repeat, RNA binding protein 1/CUGBP Elav-like member 1) synergistically inhibit cyclindependent kinase 4 (CDK4) translation in normal IECs by recruiting the Cdk4 mRNA to processing bodies (12).…”
Section: Transgenic Expression Of Mir-222 Disrupts Intestinal Epithelmentioning
confidence: 99%
“…Recent evidence suggests that ESR1 is a direct target of miR-222 with a specific site at the seed sequence of this miR (Rao et al 2011). Furthermore, high E2 concentrations in visceral adipocytes upregulate miR-222 transcript levels and downregulate Esr1 and Glut4 transcript levels (Shi et al 2014). By contrast, Esr2 has been found to control Glut4 transcription via DNA methylation in induced murine adipocytes (Rüegg et al 2011).…”
Section: Insulin Sensitivitymentioning
confidence: 99%
“…miRNAs have been shown to participate in the carcinogenesis of several types of tumors, and they can impair cellular movement, invasion, growth and proliferation, thus promoting the development of tumors [42]. miRNAs are also expressed in the placenta and have been reported in pregnancy complications including GDM and preeclampsia [21,43]. Fu et al identified a series of miRNAs that were involved in dysregulated placental development and function [44].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on trophoblasts have suggested that miRNAs are involved in proliferative, migratory and invasive processes [19]. Many differentially expressed miRNAs have been identified based on hybridization, qPCR, and sequencing analysis in the GDM placenta or serum [20,21]. Recently, Bari et al performed specific mRNA sequencing with trophoblast isolated from the GDM placenta and indicated that placental trophoblasts of GDM were biologically different from those in the control group at the gene expression level [22].…”
Section: Introductionmentioning
confidence: 99%